Changes In The Inclınatıon Of The Occlusal Plane Wıth Begg Technıque Treatment In Deep Bıte Cases - Mirzen Arat; Ayşegül Köklü; Erhan Özdiler; Haluk İşeri (Turkish Journal of Orthodontics, 1988)

(untitled)
The aim of this study was to investigate the changes in the inclination of the occlusal plane with treatment in skeletal class II deep bite cases. The sample consisted of 40 lateral cephalometric films of 20 individuals. 10 of these 20 were treated with Begg technique and the other 10 were only observed without any orthodontic treatment. 12 parameters had measured on every lateral cephalometric film. Differences between treatment and control groups were compared by student t-test. As a result, there was no statistically difference in the inclination of occlusal plane between treatment and control groups. The inhibition of vertical growth of the lower alveolar process with treatment was an important factor for opening the bite.